New teaching methods in modern conditions for art students - Dadyrova, Assel A. (Human in the Socio-Cultural Dimension, 2022)
An attempt is made to analyse new teaching methods in new conditions in the modern world. Non-classical teaching methods for art students, methodological recommendations for conducting classes are considered. The article presents approved author’s developments – cases, mobile practical seminars. Based on extensive methodological material, innovative pedagogical ideas and implemented cases in the educational process are analysed, and how, through new teaching methods, taking into account the specifics of art education, the developed pedagogical technologies are applied.